(untitled) (Research, Society and Development, 2020)
The aim of this study was to evaluate the physiological and growth responses of watermelon under application of NPK rates using different proportions of mineral and organic fertilizers. The experiment was taken place in an area located at the Federal University of Campina Grande (UFCG), Campus Pombal - PB (6º48’16’’ S and 37º49’15’’ W), during the period from June to September 2013. The treatments consisted of three nutrient concentrations of N, P and K (50, 100 and 150% of NPK recommendation for watermelon) and five proportions of mineral and organic fertilizer (100/0, 75/25, 50/50, 25/75 to 0/100). The design was a randomized block in factorial scheme 3 x 5, with four replications. The amount of 100 % was the corresponding NPK 120 kg ha-1, respectively, for N, P and K. They were evaluated: gas exchange, leaf dry matter, stem, fruit and leaf area. The concentration of 150 % of the recommended NPK to the culture of watermelon was the most effective in increasing the physiological characteristics and dry matter accumulation in stem, leaf, fruit, and leaf area. The combined application of mineral and organic fertilizer provides equivalent photosynthetic rate isolated application of mineral fertilizer with an 50/50 ratio the most effective for this variable. The proportions 75/25 and 50/50 were the most efficient in dry matter accumulation in watermelon.